2022
DOI: 10.1111/jocs.16460
|View full text |Cite
|
Sign up to set email alerts
|

Rotation characteristics and neo‐commissural alignment of transcatheter heart valve in type‐0 bicuspid aortic valve

Abstract: Aims This study sought to characterize the rotation of the transcatheter heart valve (THV) and evaluate the neo‐commissures overlap with coronary arteries in type‐0 bicuspid aortic valve (BAV). Methods and Results This was a single‐center, 10‐patient, retrospective observational cohort. Pre‐TAVI computed tomography and procedural fluoroscopy were analyzed. Coplanar fluoroscopic views were coregistered to pre‐TAVI computed tomography to characterize THV rotation and determine coronary overlap. The incidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…If the centre marker is closed to or overlapped with the left one on the fluoroscopic image, we will withdraw the delivery system to the descending aorta and rotate the delivery system 180°, then readvance the THV to the aortic annulus. The neo-commissural alignment or mild commissural misalignment was obtained in all five cases present in our study, although the THV rotated in the deploying phase by some degrees [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the centre marker is closed to or overlapped with the left one on the fluoroscopic image, we will withdraw the delivery system to the descending aorta and rotate the delivery system 180°, then readvance the THV to the aortic annulus. The neo-commissural alignment or mild commissural misalignment was obtained in all five cases present in our study, although the THV rotated in the deploying phase by some degrees [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…If percutaneous coronary intervention is required after transcatheter aortic valve replacement (TAVR), coronary access will be more challenging when transcatheter heart valves (THVs) commissural posts face a coronary orifice, particularly with self-expanding valves [ 1 ]. Venus-A plus THV (Venus Medtech Inc, Hangzhou, China) has three inflow markers that are in alignment with the nadirs of THV sinuses ( Figure 1 ) [ 2 , 3 ]. Our previous study showed that neo-commissural alignment could be evaluated by observing the three markers of the Venus-A plus THV (3).…”
Section: Introductionmentioning
confidence: 99%
“…5,7,8 Recently, Bieliauskas et al 9 Commissural alignment of THV in patients with bicuspid aortic valve (BAV) is even more challenging given the complex aortic root anatomy frequently found in these cases. Therefore, Chen et al 10 are to be congratulated to have come up with a specific commissure-middle view technique to optimize commissural alignment in THV in type-0 BAV. This was a retrospective observational study of patients undergoing TAVR with the selfexpandable Venus A-Valve (Venus MedTech).…”
mentioning
confidence: 99%